Data Mining: Techniques and Applications in the Manufacturing Industry - Al-Nimer, Thaer (2006)
Data mining and knowledge discovery in databases are increasingly attracting a significant number of academics, professionals, and the attention of the media. It is regarded by many industrial organisations as an important tool in knowledge discovery with the potential for substantial profits. However, data mining is a relatively new field that has emerged as a result of advancements in many different subjects such as statistics and computing and has only recently began to attract the attention it deserves.